IMPROVED THERMOACOUSTIC COMPUTED TOMOGRAPHY SCANNER - KRUGER, ROBERT A (2000)
Methods and apparatus for measuring and characterizing the localized electromagnetic wave absorption properties of biologic tissues (29) in vivo, using incident electromagnetic waves to produce resultant acoustic waves. Multiple acoustic transducers (33) arranged on a rotatable imaging bowl (14) are acoustically coupled to the surface of the tissue for measuring acoustic waves produced in the tissue when the tissue is exposed to a pulse of electromagnetic radiation. The multiple transducer signals are then combined to produce an image of the absorptivity of the tissue, which image may be us ed for medical diagnostic purposes. Specific mathematical reconstruction procedures are described for producing images from transducer signals. Specific arrangements of transducers are illustrated, and noise reduction techniques are described.